Curriculum Dynamics and Existence of PAI: Challenges and Synergy Opportunities in Strengthening Student Character - Susetyo, Marwal Blantara; Fakhruddin, Agus; Helmy, Helmy Abdullah; Dzakiya , Mifta Ghina; Husaeni , Muhammad Fahri Ali (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
Islamic Religious Education (IRE) within the national education system faces structural challenges that are both technical-curricular and ideological-pedagogical. This study analyzes the dynamics of IRE's existence and formulates a synergistic model to strengthen student character development through a Literature Review of 13 selected articles using a Critical Content Analysis lens. Findings reveal that technical challenges include limited instructional time and overlapping values across subjects. Meanwhile, more fundamental ideological challenges stem from the epistemological dichotomy between religious and general sciences and the dominance of transmissive teaching (